Ethics and public policy a philosophical inquiry - Wolff, Jonathan (Routledge, 2020)
An ideal introduction for those coming to philosophy, ethics or public policy for the first time, and a vital resource for anyone grappling with the moral complexity underlying policy debates. The 2nd edition includes four new chapters and has been revised and updated throughout.